A nitrogén és kálium szerepe a hibridbúza tápanyag-ellátásában - Poós, Tamás; Sárdi, Katalin; Zsittnyán, Tamás (GEORGIKON FOR AGRICULTURE, 2018)
Wheat (Triticum aestivum L.) is one of the main crops in the world and in Europe. Due to the results of breeding and the improved agrotechnics, both yield levels and quality can be more favourable. This is more typical since the proportion of hybrid wheat is increasing. Outstandingly high yield potential of hybrid wheats may decrease the problems of continuously increasing nutrient demand on the global scale. The effects of increasing N and K rates were studied in a small plot experiment separated in a field of the University of Pannonia, Georgikon Faculty, Keszthely.The main vegetative parameters and nutrient concentrations of leaf samples at the stage of heading of the hybrid wheat (Hybiza) were investigated. At the harvest, yield quantities and and the main parameters of yield quality (e.g. moist gluten content) were determined. From the results it was established that effects treatments have resulted in significant increases in both yield quantity and quality parameters. Highest yield level was obtained as a result of split application of N in three times while maximum values of gluten content (27.25%) were observed with increased K content and split application of N in twice, reaching the Euro quality range of B1-B2.  Based on the results of this experiment it was concluded that with proper nutrient management, both yield level and good quality criteria can be achieved in hybrid wheat production.
Keywords: field experiment; hybrid wheat; nutrient management; nitrogen; potassium